Social and communication skills in english through virtual or simulated environment - Wan Mansor, Wan Fara Adlina; Zakaria, Mohamad Hassan; Mustaffa, Faizal Yamimi (Universiti Teknologi Malaysia, 2004)

(untitled)
Virtual world or environment such as MOO (MUD- Multi-User Domain,Object Oriented) is one of the predominantly text-based synchronous Computer Mediated Communication (CMC) tools. Since early 1990s, MOO has generated much interest among second language researchers. However, to date, not many studies have focused on the impact of using MOO on face-to-face communication skills. For the purpose of this research, in UTM, a full-fledged virtual university called UniTekMOO, was developed and regularly updated to benefit the students in their English communication skills and specific areas of study. With the construction of the virtual campus of UnitekMOO, this study began investigating on the effects of MOO on learners’ communication skills and on their attitudes towards English language learning. Data were gathered through participant observation (done virtually), classroom observation, questionnaire and online interview. Content and conversational analysis were also done on the MOO chatlogs. Through interviews and questionnaires, learners believed that their interaction experiences within the MOO had improved their communication skills. In particular, more than half of the students felt that their interactions within the MOO environment have i) boosted their interest in learning English, ii) helped improve their spelling, and iii) increased their confidence in face-to-face interactions in English. We would recommend that the UnitekMOO be made available to students to practice using the target language as activities to complement their regular English proficiency classes.